André Malraux and Romain Gary as the Writers of Adventure and Metamorphosis - Labouret, Denis (Literatūra, 2022)
Among the French novelists of the 20th century, André Malraux and Romain Gary stand out for their practice and thought of adventure, at a time when individual adventure seems to be condemned by collective history. On this point, their works show clear convergences. Each of them, in fact, testified in his work to a life of “active adventurer”. Each of them built a work in which adventure, as a spring of action or as a theme of reflection, occupies a major place. La Voie royale and Les Conquérants, Les Racines du ciel and La Promesse de l’aube bear the mark of these convergences between two authors who are known to have frequented and appreciated each other. Moreover, according to both of them, the adventurer is in search of metamorphosis because he suffers from being locked up in the prison of identity. He seeks in adventure an experience of otherness which alone allows him to exist fully, by changing his “skin”. In this respect, much of Gary’s work seems to illustrate Malraux’s definition of the adventurer in the preface to Le Démon de l’absolu. But while Malraux moves away from the novelistic genre and turns, from 1945 onwards, to a reflection on art that gives adventure and metamorphosis an essentially aesthetic meaning, Gary does not cease to confer on adventure a profoundly existential meaning and goes so far as to situate it at the very heart of the creative process of the novel. This vision of adventure, which he develops in particular in his essay Pour Sganarelle, culminates in this ultimate adventure which will be accomplished, with the invention of Émile Ajar, in a totally new metamorphosis of the author. This discrepancy may provide an element of explanation for the differences that can be observed today between the reception of Malraux, who seems to be on the decline, and that of Gary, which is much more flourishing.
Keywords: Adventure; history; identity; metamorphosis; novel